GIS -Based Multi-Hazard Disaster Risk Mapping in The Indonesian Capital City (IKN) Area - Auliah Mujahidah; Najma Nur Mawaddah; Aisyah Trees Sandy; Yulian Widya Saputra (JPG (Jurnal Pendidikan Geografi), 2026)
This study employs a quantitative approach to comprehensively map and analyze multi-hazard disaster risks in the Indonesian Capital City (IKN) area, with a primary focus on flood and landslide threats. The research involved extensive data collection through field surveys, direct observations, documentation, and the acquisition of geospatial datasets to ensure accurate representation of the study area. The collected data were analyzed using a combination of scoring techniques, map overlays, and disaster risk classification methods. All analyses were conducted using Geographic Information System (GIS) software to produce a detailed thematic risk map. In accordance with the Regulation of the Head of BNPB Number 2 of 2012 concerning general guidelines for disaster risk assessment, the study classified hazard risks into three categories: low, medium, and high. Spatial analysis results indicate that low-risk areas occupy 76,576.37 hectares, approximately 57.47% of the total study area. Moderate-risk areas cover 11,131 hectares or 7.63%, while high-risk areas account for 58,236.45 hectares, approximately 39.90%. These findings highlight significant variations in vulnerability and hazard exposure across the IKN region. The produced multi-hazard map serves as a crucial tool for development planning and disaster risk mitigation, providing essential information for local authorities, urban planners, and policymakers. By identifying areas with different levels of risk, this study contributes to enhancing community safety, protecting critical infrastructure, and supporting sustainable development in the IKN area. The comprehensive spatial approach ensures that disaster preparedness strategies are grounded in scientific analysis and real-world data, offering a foundation for proactive risk management and long-term resilience.